2016
DOI: 10.1136/jclinpath-2016-203718
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A family expression is correlated with poor survival of patients with lung adenocarcinoma: a retrospective clinical study based on tissue microarray

Abstract: Molecular assessment of MAGE-A family members could be considered to improve the prognostic evaluation and to provide a new potential therapeutic strategy for patients with LAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The survival analysis revealed that a high level of MAGE-A1 expression was correlated with unfavorable outcomes of LUAD. All the above data concurred with the studies that showed high expression levels and a prognostic role of MAGE-A1 in LUAD [43, 45, 46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The survival analysis revealed that a high level of MAGE-A1 expression was correlated with unfavorable outcomes of LUAD. All the above data concurred with the studies that showed high expression levels and a prognostic role of MAGE-A1 in LUAD [43, 45, 46].…”
Section: Discussionsupporting
confidence: 90%
“…As a member of the MAGE-A antigens, which are the best characterized CTAs, MAGE-A1 is also strictly tumor-specific and is detected in various solid tumors [40–42]. Although MAGE-A1 expression in LC has also been reported [4345], the detailed and exclusive function of MAGE-A1 in LUAD remains unclear. After MAGE-A1 was screened as the most promising candidate by the aforementioned bioinformatics analyses, a set of investigations was performed to thoroughly examine the characteristics of MAGE-A1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-34a has been reported to regulate carcinogenesis by targeting several mRNAs, including MAGE-A in medulloblastoma (22), programmed cell death 1 ligand 1 or lactate dehydrogenase A in breast cancer (28), and B cell lymphoma-2 in cervical cancer (29). The expression of MAGE-A has been documented to be upregulated in gastric cancer (35), epithelial ovarian cancer (36), and lung adenocarcinoma tissues and cells (37). In agreement with the aforementioned studies, the results of the RT-qPCR analysis in the present study revealed that the mRNA level of MAGE-A was significantly upregulated in RB tissues compared with paracarcinoma tissues (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…TMAs construction, HE and IHC staining were performed and analyzed as described in our previous study [ 57 ].…”
Section: Methodsmentioning
confidence: 99%